Extraction, characterization and evaluation of antibacterial activity of essential oil of Senecio graveolens Wedd (Wiskataya) - Ochoa Pumaylle, Kiev (2012)
The aim of this work was extract, characterize and evaluate the antibacterial activity of the essential oil of Senecio graveolens Wedd (Wiskataya) against Escherichia coli and Staphylococcus aureus ATCC 29923. The leaves and stems of S. graveolens were collected in the district of Puquio 3800 m.s.n.m., Lucanas province, and department of Ayacucho. The essential oil was obtained by steam water destilation dried leaves and stems with yield 1.26% (w/w) to which physical testing were performed. The chemical composition was evaluated by gas chromatography with mass detector (GC-MS). Antibacterial activity of S. graveolens oil was tested by agar diffusion method in wells against Gram positive strains such as S. aureus ATCC 29923 and Gram negative as E. coli. The density a 20 ºC was 0.8755 g/ml; the index refraction was 1.4726 and the rate rotation was 102° 85' and the solubility miscible in ethanol. The GC-MS showed the main components sabinene (52.39 %), (+)-4-carene (8.20 %), τ-terpinen (7.11 %), β-myrcene (6.74 %), 4-terpinenol (3.78 %) and pulegone (3.67 %). The results showing activity strong antibacterial activity and moderate, respectively, for the strains tested, observing formation of inhibition halos for essential oil concentrations at 80, 90 and 100 % in both strains. The essential oil of S. graveolens presented with promising antibacterial activity.